2018
DOI: 10.1080/14397595.2018.1533514
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of weekly subcutaneous tocilizumab monotherapy in patients with rheumatoid arthritis who had an inadequate response to subcutaneous tocilizumab every other week: Results from the open-label extension of the SHINOBI study

Abstract: Yamakawa & the SHINOBI Study Group (2019) Long-term safety and efficacy of weekly subcutaneous tocilizumab monotherapy in patients with rheumatoid arthritis who had an inadequate response to subcutaneous tocilizumab every other week: Results from the open-label extension of the SHINOBI study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The combined results indicate that the IL-6R/STAT3 signaling axis is preferentially but not exclusively active in ABC-DLBCL, and a negative prognosticator for both subtypes; STAT3 phosphorylation correlates with activation of the upstream kinase JAK2. IL-6R is a therapeutic target in rheumatoid arthritis (RA); a neutralizing antibody targeting the IL-6R, tocilizumab (trade name: Actemra), is approved for the treatment of RA in adult patients (Ogata et al, 2012(Ogata et al, , 2018 and has also recently received FDA approval for the treatment of cytokine release syndrome related to CAR T-cell therapy (Le et al, 2018). We sought to examine a possible benefit of tocilizumab monotherapy in MISTRG6 mice that harbor spleen-and bone marrow-colonizing lymphomas due to intravenous transplantation of serially passaged primary DLBCL cells; this patient-derived xenograft is positive for the IL-6R and also positive for phosphorylated STAT3 (Fig 4).…”
Section: Il-6 Signaling Contributes To Myc-driven Lymphomagenesis In mentioning
confidence: 99%
“…The combined results indicate that the IL-6R/STAT3 signaling axis is preferentially but not exclusively active in ABC-DLBCL, and a negative prognosticator for both subtypes; STAT3 phosphorylation correlates with activation of the upstream kinase JAK2. IL-6R is a therapeutic target in rheumatoid arthritis (RA); a neutralizing antibody targeting the IL-6R, tocilizumab (trade name: Actemra), is approved for the treatment of RA in adult patients (Ogata et al, 2012(Ogata et al, , 2018 and has also recently received FDA approval for the treatment of cytokine release syndrome related to CAR T-cell therapy (Le et al, 2018). We sought to examine a possible benefit of tocilizumab monotherapy in MISTRG6 mice that harbor spleen-and bone marrow-colonizing lymphomas due to intravenous transplantation of serially passaged primary DLBCL cells; this patient-derived xenograft is positive for the IL-6R and also positive for phosphorylated STAT3 (Fig 4).…”
Section: Il-6 Signaling Contributes To Myc-driven Lymphomagenesis In mentioning
confidence: 99%
“…In the MRA229JP study, which was a study evaluating the efficacy and safety of TCZ-SC (162 mg every 2 weeks) versus TCZ-IV (8 mg/kg every 4 weeks) in patients with rheumatoid arthritis, it was suggested that serum TCZ trough concentrations tended to decrease with increasing body weight, body surface area, and body mass index (BMI). American College of Rheumatology 20 responses were consistently lower in patients treated with TCZ-SC than in patients treated with TCZ-IV in patients with body weight ≥70 kg or BMI ≥25 kg/m 2 [ 10 ]. In fact, the BMI of the patient in Case 6 was 32.3 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations to this study. First, although subcutaneous injection of tocilizumab every week (QW) has been approved since June 2017 in Japan for treatment of RA with inadequate response to subcutaneous injection every other week, 43 44 no patients participating in this study were treated with the QW dosing regimen of tocilizumab. If we had used the QW in this study, more favourable outcomes might have been induced in the tocilizumab group.…”
Section: Discussionmentioning
confidence: 99%